“Overview of the Managerial Functions and Competencies of Human Resource Management in Local Female The Biak Berek Ikat Weaving Group” - Burin, Stefanie Noviega Bribin; Mau, Ignatia Thomasita Bau; Firmansyah, Mariano (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2025)
The Bia Berek Group is a business unit that produces and sells weaving in Belu Regency. In this research, the managerial function factors of human resource management (HR) and human resource competence (HR) will be looked at. The managerial function of human resource management consists of planning, organizing, directing and controlling. Meanwhile, HR competencies consist of skills, knowledge, abilities and personal characteristics. This research uses qualitative methods, based on interviews and observations. Interviews were conducted with 10 members of the Bia Berek ikat weaving group. The results of this research are different from the proposition that has been proposed, namely that managerial function and human resource (HR) competence are important factors in the success of the Bia Berek weaving group business.